Budidaya Jamur Tiram sebagai Usaha Alternatif bagi Masyarakat (Pelatihan di Desa Bale Kencana, Kecamatan Mancak) - Aryanti Dwi Untari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
The aim of the Community Service Program to increase public awareness and understanding of the potential it has to improve its quality of life. The problem faced is the economy of the community that relies on garden products and melinjo harvest, so it is necessary to have an alternative effort to improve the economy of the people of Bale Kencana Mancak Village. The method of implementing this service is through (1) Surveying through observation, interviews, and analysis of village potentials and problems, (2) Training of oyster mushroom cultivation, (3) Mentoring of oyster mushroom cultivation practices. The result of this program is that the community obtains knowledge and skills of oyster mushroom cultivation, so that it can make oyster mushroom cultivation as an alternative business choice to improve the community's economy.